Multiple dependent state repetitive group sampling plan for Burr XII distribution. Issue Volume 28:Issues 2(2016) (2nd April 2016) - Aslam, Muhammad; Azam, Muhammad; Jun, Chi-Hyuck
ABSTRACT: In material engineering application, the failure time of material due to weakness in material (fatigue) is usually caused by repeated variations of stress. The failure time is modeled by statistical distributions. In this article, an attribute multiple state repetitive group sampling plan is developed assuming that the life time follows the Burr Type XII distribution. The plan parameters are determined by considering two points on operating characteristic (OC) curve. Tables are given for the practical use. The advantages of the proposed plan are discussed over the single sampling plans. Examples are given to illustrate the proposed plan.